Invincibility threatens vaccination intentions during a pandemic - James M. Leonhardt (Public Library of Science (PLoS), 2021)
Some people feel they are invincible to the novel coronavirus SARS-CoV-2 (COVID-19). They believe that being infected with COVID-19 would not be a serious threat to their health. While these people may or may not be correct in their personal risk assessment, we find that such perceived invincibility may undermine community efforts to achieve herd immunity. Multi-level analysis of survey respondents across 51 countries finds that perceived invincibility from COVID-19 is negatively associated with believing there is a need to prevent the spread of COVID-19 in one’s community (n = 218,956) and one’s willingness to inoculate against the disease (n = 71,148). These effects are most pronounced among individuals from countries lower in cultural collectivism (e.g., USA, UK, Canada) and highlight the need to consider the interplay of individual and cultural factors in our efforts to understand, predict, and promote preventative health behavior during a pandemic.